Overview And Challenges Of Operating Foreign Banks In Kish Free Trade Zone - Rahimi, Nazila (2009)
This research is related to the presence of foreign bank in Kish Free Zone and the challenges in operating foreign bank. Also concerns about the ultra-boarder banking as a solution for absorbing foreign banks and financial institutes.